MENGURANGI SKOR STRES MELALUI DUKUNGAN TEMAN SEBAYA (PEER SUPPORT) PADA MAHASISWA PRAKTIK PROFESI NERS - Popy, Popy; Rosdiana Tandiola (Journal of Innovation Research and Knowledge, 2025)
Nursing students, both undergraduate and postgraduate, have a higher risk of experiencing stress compared to students from other programs. Prolonged stress that is not handled will potentially have negative effects. One of the interventions to reduce stress scores in nursing students during clinical practice is to provide support from friends (peer support). Peer support is a relationship between a senior (usually more experienced) who provides support to junior students (who usually have limited experience) with the aim of supporting positive personal development in clinical practice. Objective: to determine the effect of peer support on reducing stress scores in nursing clinical practice students. Research method: This study used a research design using (quasi experimental) one group pretest-posttest design. The study was conducted at the Faculty of Nursing, a Private University in Jakarta, with a sample size of 44 respondents, and the study lasted for 4 weeks. Stress scores were measured using the perceived stress scale (PSS) instrument. Results: The test used was the paired T test. The results of the study showed that before the peer support intervention, the majority of respondents (54.5%) experienced moderate stress with a mean score of 76.14, while after the peer support program intervention, the majority of respondents (86.4%) were in the non-stress category with a mean score of 35.30. There was a decrease in stress scores of 40.84 with a p value of 0.000 (<0.05) and a 95% CI value of 38.78 - 42.89